Changes in land-use and their impact on erosion rates and overland flow generation in the Maghreb region - Coelho, C.; Ferreira, A.; Laouina, A.; Boulet, A.-K.; Chaker, M.; Nafaa, R.; Naciri, R.; Regaya, K.; Hamza, A.; Carvalho, T.; Keizer, J. (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2004)
The ongoing intensification of grazing as well as the replacement of traditional land management systems in the Maghreb has brought to the forefront the fundamental role of land-use in determining soil erosion hazard. This paper reports on erosion rates and soil hydrological characteristics of a variety of land uses in Morocco and Tunisia. The results were obtained through rainfall simulation experiments carried out in the field using a portable simulator, following the design of CERDÀ et al. (1997).Traditional land management systems - typically involving a combination of agriculture, animal husbandry and forestry - produced the least amounts of overland flow and the lowest soil erosion rates. Over-exploitation of these systems apparently has only minor hydrological and erosional impacts. Heavily grazed, degraded "maquis" shrublands, on the other hand, produced considerable amounts of overland flow. At the plot scale of the rainfall simulation experiments (0.24 m2), the corresponding sediment loads are rather insignificant. Nevertheless, slopes where "maquis" shrublands (which generally have very compacted soils) occur upslope from more erodible soils may present a major erosion hazard.